2018
DOI: 10.1007/s00784-018-2471-5
|View full text |Cite
|
Sign up to set email alerts
|

The ratios of pro-inflammatory to anti-inflammatory cytokines in the serum of chronic periodontitis patients with and without type 2 diabetes and/or smoking habit

Abstract: CP and CP associated with hyperglycemia and/or smoking might contribute to a systemic inflammatory burden and increased risk of systemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 50 publications
6
36
0
1
Order By: Relevance
“…We detected IL-4, IL-6, IL-10, IL-17F, IL-33 and TNF-α; however, no statistically significant differences were found between the groups. Our data on IL-4, IL-6, IL-10 and TNF-α data are in line with several previously published papers [6,21,22], although significant differences in serum cytokines between healthy controls, aggressive and chronic periodontitis have been reported [6,[22][23][24].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We detected IL-4, IL-6, IL-10, IL-17F, IL-33 and TNF-α; however, no statistically significant differences were found between the groups. Our data on IL-4, IL-6, IL-10 and TNF-α data are in line with several previously published papers [6,21,22], although significant differences in serum cytokines between healthy controls, aggressive and chronic periodontitis have been reported [6,[22][23][24].…”
Section: Discussionsupporting
confidence: 93%
“…A different study, however, reported no differences in the serum level of IL-1β between chronic periodontitis and healthy control groups [21]. Our data on IL-4, IL-6, IL-10 and TNF-α data are in line with several previously published papers [6,21,22], although significant differences in serum cytokines between healthy controls, aggressive and chronic periodontitis have been reported [6,[22][23][24]. We detected IL-4, IL-6, IL-10, IL-17F, IL-33 and TNF-α; however, no statistically significant differences were found between the groups.…”
Section: Discussionsupporting
confidence: 92%
“…Lower concentration of IFN-γ could favor an uncontrolled infection or/and leading to more tissue damage. Added to this, IL-4 levels were lower in patients with slight PD when compared to controls, and this was consistent with previous studies [90,91]. Lower IL-4 levels were also found when PD patients had smoking habits and/or diabetes [91].…”
Section: Discussionsupporting
confidence: 92%
“…Added to this, IL-4 levels were lower in patients with slight PD when compared to controls, and this was consistent with previous studies [90,91]. Lower IL-4 levels were also found when PD patients had smoking habits and/or diabetes [91]. IL-4 produced at sites of infection can induce Th2 lymphocyte differentiation and activate antibody production by B cells and inhibit the Th1 response [92]; the Th2 response decreased bone loss in PD [93].…”
Section: Discussionsupporting
confidence: 89%
“…Another hallmark of the two diseases is dysregulation of the local (periarticular/periodontal) and systemic cytokine production, to a significant extent reflecting the aberrant immune response. Respective data have been presented in RA [12] and PD [13][14][15]. Particularly in RA, local and systemic cytokine profiling ultimately facilitated the introduction of new therapeutics, the biologics, which act in a more selective manner than conventional disease-modifying anti-rheumatic drugs (cDMARDs) such as methotrexate and leflunomide.…”
Section: Introductionmentioning
confidence: 99%